Metallic 1T-WS2 for Selective Impedimetric Vapor Sensing - Yong, Alex Sheng Eng (2017)
Selective gas sensing is of immense importance for industrial as well as safety purposes. Here it is shown that metallic 1T phase transition metal dichalcogenides, such as tungsten sulfide (WS2), provide sensitive and selective platform for gas sensing. Using impedance spectroscopy distinguishable alterations can be detected on the impedance phase spectrum of interdigitated gold electrode modified with chemically exfoliated 1T-WS2 caused by different vapors. In particular, it is found that the impedance phase spectra of 1T-WS2 device present different resonant frequencies with maximum around 1 Hz in the presence of methanol vapor and around 1 kHz in the presence of water vapor. Such a well-distinguished signal allows their selective detection also when they are present in a mixture. The impedance phase spectra allow the selective methanol and water vapor sensing with an impedimetric device based on 1T-WS2. This system utilizing 1T phase of WS2 for selective gas sensing based on impedance spectroscopy opens new avenues for gas sensing and shall find wide spectra of applications.